PROBLEMS OF BRINGING MINORS TO ADMINISTRATIVE LIABILITY IN THE RUSSIAN FEDERATION - Suslova, Galina; Tomashevskaya, Natalya; Kuvyrchenkova, Tatyana; Gaidashov, Alexander; Redikultceva, Elena (Revista Inclusiones, 2020)
The article is devoted to the problems of bringing minors to administrative liability in the Russian Federation. The feature of administrative liability of persons who have not reached the age of majority is related to the special subject of proceedings on administrative offenses, the features of bringing this category of offenders to justice, and the applied measures of responsibility, where attention is focused on educational and preventive impact. It has been proved that one of the key components of social policy regarding minors should be the improvement of the activities of juvenile commissions. It has been revealed that this process needs to be supplemented by promoting the idea of strengthening the role of the law and protecting the rights of minors at the federal and regional levels, as well as involving citizens and their associations in solving socially significant problems.